CIVIL LIABILITY OF THE STATE FOR OMISSION IN ENVIRONMENTAL DISASTERS - Herrera Sarti, Juliana; Villela Florêncio, Stella (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to study state accountability in the face of omission in environmental disasters. To this end, the civil liability institute was studied, both in general, as well as its species and necessary assumptions to characterize the duty to indemnify. The general aspects of the environment were approached and the socio-environmental rule of law and its environmental protection duties were discussed, presenting environmental policies and their historical evolution. Still, as a result of the environmental damage generated, the state civil liability institute was studied in a specific way, pointing out important aspects, thus reaching the focus of the work by analyzing which type of civil liability could be applied and on which theory it would be based. case of failure by the State to face environmental disasters. It is concluded, according to the environmental legislation, that the State has an essential responsibility to protect the whole or the Environment and a society from environmental disasters through effective and efficient inspections of the activities of individuals, so that if it does not do so it must be held responsible for the loss of the damage, and may even be jointly and severally liable for damages. In light of the largest environmental accident, commonly known as the Mariana dam, the State’s omission was evidenced by waves, it is expected that it will change its methods of conduct and prepare better to deal with environmental issues, really boosting its police power to prevent new disasters from happening by their mere inertia.